Family-Based Consent and Motivation for Cadaveric Organ Donation in China: An Ethical Exploration - Fan, Ruiping (J Med Philos, 2019)
This essay indicates that Confucian family-based ethics is by no means a stumbling block to organ donation in China. We contend that China should not change to an opt-out consent system in order to enhance donation because a “hard” opt-out system is unethical, and a “soft” opt-out system is unhelpful. We argue that the recently-introduced familist model of motivation for organ donation in mainland China can provide a proper incentive for donation. This model, and the family priority right that this model supports, is ethically justifiable in terms of Confucian family-based ethics.